P-137 YI Citrobacter Rodentium and Social Stressor Exposure Impacts Colonic Inflammation and Short Chain Fatty Acid Receptor Expression. (March 2016) - Maltz, Ross; Keirsey, Jeremy; Mackos, Amy; Kim, Sandra; Somogyi, Arpad; Bailey, Michael
Abstract : Background: Inflammatory bowel diseases (IBD), which include Crohn's disease and ulcerative colitis, are chronic relapsing diseases that affect the gastrointestinal tract. Dietary and environmental factors, such as exposure to stress, have been suggested to impact the severity of IBD, but the mechanisms by which this occurs are not yet clear. However, exposure to stressors has been shown to impact inflammatory cytokines and chemokines, and to change the composition of the gut microbiota. Short chain fatty acids (SCFA) are produced by gut microbiota, and activation of SCFA receptors has been shown to influence the acute inflammatory response to colonic pathogens. However, it is not yet known whether stressor -induced changes in the microbiota, colonic inflammation, and SCFA production are related. Methods: Male specific pathogen-free C57BL/6 mice 6 to 8 weeks old were fed standard laboratory chow and were either infected with C. rodentium or left uninfected as a control group. In addition, mice were either exposed to a Social Disruption (SDR) stressor or left undisturbed. SDR involves repeated social defeat over a 2 hours period, beginning one day prior to infection and repeated on 6 consecutive days. Mice were either sacrificed on day 6 or day 12 post-infection. Semi-quantitative real time PCR was performed on proximal colonic tissue to assess the expression of inflammatory cytokines (including TNF-α, IL-1β, and iNOS) and anti-inflammatory cytokines (TGF-β and IL-10). Real time PCR was also performed to assess mRNA levels of SCFA receptors GPR41, GPR43, and GPR109. Fecal samples taken from the colon on the day of the sacrifice were extracted to quantify SCFA levels (acetic, butyric, and propionic acids) by gas chromatography-mass spectrometry (GC-MS). Results: Exposure to the stressor exacerbated C. rodentium—induced iNOS, TNF-α, IL-10, and IL-1β mRNA ( P < 0.05), and there was significantly worse histology scores ( P < 0.05). C. rodentium infection resulted in reduced GPR43 receptor mRNA expression ( P < 0.05). Infection also increased the expression of GPR41 and GPR109A receptor mRNA, but only if the mice were also exposed to the SDR stressor ( P < 0.05). Butyric and propionic acid levels were increased in mice that were infected, and exposure to the stressor further increased propionic acid levels ( P < 0.05). There was an increase in acetic acid in infected mice that were exposed to the stressor, whereas infection in the absence of the stressor did not affect acetic acid. Conclusions: Stressor exposure significantly changes the production of SCFA, and the expression of their receptors, in the absence or presence of pathogen challenge. These changes were associated with increased colonic inflammation, but whether changes in SCFA directly contribute to enhanced colonic inflammatory responses in stressor-exposed mice is not yet known. Our data indicate that murine infection with C. rodentium is an appropriate animal model to further study the impact of SCFA and receptor signaling on the severity of colonic inflammation.